RELATIONSHIP BETWEEN OVERVIEW OF FOREIGN TOURIST VISITS AND HUMAN DEVELOPMENT INDEX (IIDI) AFTER THE TSUNAMI UNTILL THE COVID-19 PANDEMIC ON REGIONAL ECONOMIC GROWTH IN ACEH PROVINCE - Yayuk Eko Wahyuningsih, Yasrizal , Ishak Hasan, T. Zulham (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Since the Covid-19 virus was declared a pandemic by the WHO in 2020, the number of cases has continued to increase over time. In Indonesia, the total number of Corona virus cases is 95,418 people (BNPB Indonesia, 24/7/2020). Likewise in Aceh Province with 5 ,423 cases. This has a bad effect on various sectors.The tourism industry is one of them. BPS data shows that since the Covid-19 pandemic struck many countries around the world as well as Indonesia, the tourism industry has seen a decrease of up to 89 percent of international tourist visits as of August 2020, After the earthquake / Tsumani tragedy on December 26, 2004, the international tourist visit hit its peak in 2016 with 76,452 tourists. It was however, different from 2019 to mid-2020, declining to 1,902 individuals or 85.68 percent.while domestic tourists have dropped to 92.45 percent. Similarly, what happened was to the province of Aceh, which is the western tip of Sumatra province. The aim of this study is to analyze the impact of the visits of foreign tourists and the Human Development Index on economic growth in the Aceh province in 2004-2019 as the Covid-19 pandemic begins. The data used is secondary data sourced from the Provincial and West Aceh District Statistics Department and Regional Development Planning Agency Province of Aceh, so West Aceh District too. The VECM research model is the system used. Based on the results of the Granger-Causality analysis test supported by the IRF and VD analysis, the relationship between the three variables can be defined as follows: HDI has a direct effect on economic growth, where an increase in HDI will have a direct effect on increasing the value of economic growthTourism al so has a direct impact on economic development, with the growth of tourism enhancing economic growth